ปัจจัยที่มีผลต่อการตัดสินใจของผู้บริโภคในการซื้อน้ำผึ้งในพื้นที่ จังหวัดเชียงใหม่ - รัตน์ชนู อนุบัน (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The objectives of this study are; to study the attitudes of consumers towards the value of honey, to study the marketing strategies of honey entrepreneurs and vendors, and to study the factors that affected on honey purchasing decision of consumers in Chiang Mai province. The population in this study was separated into 2 groups, including honey purchasing and un-purchasing, which consist of 200 participants in each group. The data was collected using questionnaire, using analyzed Binary choice Logit Model with the alternatives of maximum likelihood estimation and marginal effect. Variables which possibly affecting on the honey purchasing decision were specified into 4 factors, including cultural factor, social factor, personal factor and psychological factor. All of the data was analyzed using descriptive statistics. This includes the study on marketing strategies, which utilized marketing mix theory, and the results of attitudes of the sample groups then were ranked by employing the Likert (Likert Rating Scale) value. The results indicated that the majority of sample populations were women. The age of honey purchasing group was ranged between 50 – 60 years old, while the non-purchasing group was ranged between 20 – 29 years old, and average income of 5,001-10,000 Baht/month. Most of the purchasing populations were freelances; in contrast, the majority of non-purchasing populations were students. For the results of attitudes on personal knowledge towards honey, the purchasing group was observed that they recognized the trademarks or brands of honey in moderate level and had the knowledge of honey background in high level. In emotional and feeling aspect; the purchasing group had the highest level of honey consumption preference. In comparison, the population of non-purchasing group had a lower level of knowledge on trademarks or brands of honey and its background. In addition, the non-purchasing group dislikes the sweetness of honey. In purchasing behavior aspect; the purchasing group revealed that they purchased honey as a gift for other people in moderate level, while, the non-purchasing group revealed that they were unsure about the honey quality, as they could not defined the differences between the real and mixed honey. Factors that affect the marketing mix strategy in distribution by the operator is found. Honey from consumer groups to focus on the highest level of products. Using the power of decision. The executives in business and access to information is beneficial. To focus on a much in public relations and packaging, and featured moderate in price retail location. Provided by sales staff for those who did not purchase a significant improvement in the price level. The packaging of entrepreneurial management and improved access to information, and a medium priority on product and publicity. The four factors that affect the decision of honey purchasing intervals at the 95% significant level showed the value of log likelihood function was -182.2618, the restricted log likelihood was -277.2589, chi squared was 189.9941 and the accuracy of the prediction was 79.25%. As the marginal effect has positive value, it can be defined to higher possibility of honey purchasing, for instance, when considering cultural factors, such as when people usually give others gifts in the special occasions or in the promotional period that the prices are decreased. The social factors may include when people living in the community usually consume honey, or explain the background and knowledge of honey to others in the community. The personal factors may include the increment of health-concern among people, in order to make themselves and their family members healthier. The psychological factors may include the popularity of trademarks or brands of honey, including its color. In contrast, if the coefficient is negative, it would result in decrement of honey purchasing; for example, when people consume honey only when they have high income. Honey consumers suggested that the producers should emphasize on health, quality, hygiene and safety in highest level. They also suggested that the price should be acceptable by consumers and the products should have the quality guarantee certificates. The results presenting in this study are consistent with the previous studies of MS. Siriluck in Purchasing Behavior of Honey and MS. Cholthira in Logit Models Analyzing.